Vivência espiritual judaica na metrópole paulistana: judeus - espíritas na contemporaneidade - Kogan, Andréa (2016)
This thesis focuses on Jews from the city of São Paulo that, besides their Jewish practices also have Spiritist rituals and practices. The backdrop is the contemporary Judaism after the Holocaust. Those researched Jews came from Eastern Europe and established themselves in Brazil after the World War II, the so-called Ashkenazim Jews. The hypothesis is the existence of a Spiritist-Judaism in São Paulo. We also investigate the lack of definition of Judaism (religion, nationality, culture, people, ethnicity, etc.) according to different thinkers, the mystical orthodox movement called Chabad-Lubavitch and its main leader, as well as characteristics of the Spiritist movement and interfaces between Spiritism and Judaism. To conclude and base the hypothesis, the field research in Jewish homes with the weekly ritual "Gospel at Home" will be described